Fixed Coefficients of Production and the Marginal Productivity Theory - Georgescu-Roegen, N. (Review of Economic Studies, 1935)
Journal Article Fixed Coefficients of Production and the Marginal Productivity Theory Get access N. Georgescu-Roegen N. Georgescu-Roegen Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 1, October 1935, Pages 40–49, https://doi.org/10.2307/2967570 Published: 01 October 1935